PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN KAWASAN EKONOMI KHUSUS SEI MANGKEI SEBAGAI KLASTER INDUSTRI - Doriani Lingga; Wahyu Ario Pratomo (Departemen Ekonomi Pembangunan USU, 2013)
The purpose of this research is to know the perception of societies to the development of Kawasan Ekonomi Khusus (KEK) Sei Mangkei as a cluster of industry. The analysis conducted in this study is a social-economy method by using 3 dimensions, which consists of the role of KEK Sei Mangkei in the development of social and economic based on investigation on the activity of PT Perkebunan Nusantara III up to now, analysis about the information dan transparency of the development of KEK Sei Mangkei, and analysis about the perception of societies about the development of KEK Sei Mangkei. The analysis is about the perception of societies comprises potency of Sei Mangkei as growth pole, relationship between KEK Sei Mangkei and social life of the societies, relationship between KEK Sei Mangkei and economic life of the societies and general perception. The analysis method uses the descriptive method, by issuing questionaires to 100 respondents surrounding the area.The result of this research shows that the PTPN III plays role in the social and economy development of local societies of Bosar Maligas District. It is realized in absorbtion of local labour and provision of facilities and infrastructures for societies. According to the greater part of respondents, the development of KEK Sei Mangkei which is now going on, is conducted transparently and involves local soceties to participate. In the perception of societies, Sei Mangkei is a potential to be a new economic growth pole by making the area becomes special economic region. They believe that the existence of SEZ Sei Mangkei will increase life standard of local societies of Bosar Maligas District. Almost all respondents agree that the development of KEK Sei Mangkei will give advantage to progress of societies, especially in increasing of societies’ social-economic standard. To sum up, most of the societies agree with the development of KEK Sei Mangkei with their main expectation that KEK Sei Mangkei will use local labour as employment so the problem of unemployment can be solved. Keywords: Special Economic Zone, industry cluster, development of social and economic, growth pole, labour absorbtion.